Effects of high-intensity blood flow testriction exercise on muscle fatigue - Neto, G. R.; Santos, H. H.; Sousa, J. B. C.; Junior, A. T. A.; Araujo, J. P.; Aniceto, R. R.; Sousa, M. S. C. (Journal of Human Kinetics, 2014)
Strength training combined with blood flow restriction (BFR) have been used to improve the levels of muscle adaptation. The aim of this paper was to investigate the acute effect of high intensity squats with and without blood flow restriction on muscular fatigue levels. Twelve athletes (aged 25.95 ± 0.84 years) were randomized into two groups: without Blood Flow Restriction (NFR, n = 6) and With Blood Flow Restriction (WFR, n = 6) that performed a series of free weight squats with 80% 1-RM until concentric failure. The strength of the quadriceps extensors was assessed in a maximum voluntary isometric contraction integrated to signals from the surface electromyogram. The average frequency showed significant reductions in the WFR group for the vastus lateralis and vastus medialis muscles, and intergroup only for the vastus medialis. In conclusion, a set of squats at high intensity with BFR could compromise muscle strength immediately after exercise, however, differences were not significant between groups.